RELIGIUSITAS, MORAL, BUDAYA LINGKUNGAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM PADA MASA PANDEMI COVID-19 - Ahmad Mukoffi; Himawan, Sukarno; Sulistyowati, Yayuk; Sularsih, Hermi; Yahfetson Boru, Aloysius (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2023)
Taxpayer compliance plays an important role in increasing state tax revenue, several factors that affect tax compliance are religiosity, morals and environmental culture. The purpose of this study was to determine the effect of religiosity, morals and environmental culture on MSME taxpayer compliance during the Covid-19 pandemic in Lowokwaru District, Malang City partially and simultaneously. This research uses quantitative methods. Determination of the sample using the Incidental Sampling technique in order to obtain a research sample of 95 MSME Taxpayers in Lowokwaru District, Malang City. The data collection technique used by the researcher is a questionnaire. The data analysis method used is multiple linear regression using the SPSS program. The results of the study prove that religiosity has a significant effect on MSME taxpayer compliance, morality has a significant effect on MSME taxpayer compliance with a tcount, and environmental culture has a significant effect on MSME taxpayer compliance. Meanwhile, jointly/combined religiosity, morals and environmental culture have a significant effect on MSME taxpayer compliance during the Covid-19 pandemic in Lowokwaru District, Malang City for what needs to be considered by MSME taxpayers, namely being obedient in paying taxes on time.